DEF6, a novel substrate for the tec kinase ITK, contains a glutamine-rich aggregation-prone region and forms cytoplasmic granules that co-localize with P-bodies - Hey, Fiona; Czyzewicz, Nathan; Jones, Peter; Sablitzky, Fred
Localization of DEF6 (SLAT/IBP), a Rho-family guanine nucleotide exchange factor, to the center of the immune synapse is dependent upon ITK, a Tec-family kinase that regulates the spatiotemporal organization of components of T cell signaling pathways and Cdc42-dependent actin polymerization. Here we demonstrate that ITK both interacts with DEF6 and phosphorylates DEF6 at tyrosine residues Tyr210 and Tyr222. Expression of a GFP-tagged Y210E-Y222E phosphomimic resulted in the formation of DEF6 cytoplasmic granules that co-localized with decapping enzyme 1 (DCP1), a marker of P-bodies; sites of mRNA degradation. Similarly treatment of cells with puromycin or sodium arsenite, reagents that arrest translation, also resulted in the accumulation of DEF6 in cytoplasmic granules. Bioinformatics analysis identified a glutamine-rich, heptad-repeat region; a feature of aggregating proteins, within the C-terminal region of DEF6 with the potential to promote granule formation through a phosphorylation-dependent unmasking of this region. These data suggest that in addition to its role as a GEF, DEF6 may also function in regulating mRNA translation.